Derecho a la defensa frente a la implementación de los medios telemáticos en la administración de justicia. - Tenesaca Aucancela, Joshue Estiven (2024)
ABSTRACT: This paper focuses on an exhaustive analysis of Ruling 2297-18-EP/23 of the Constitutional Court of Ecuador, which is notable for evaluating the violation of fundamental rights and associated legal problems, especially in telematic hearings. It examines violations of the right to defense, appeal, and access to effective justice. Refusal to participate in these hearings can affect parties' ability to exercise their defense, highlighting the need for fair participation in the judicial system. This analysis delves into the role of technology in the administration of justice, a key theme in the context of Ruling 2297-18-EP/23. It raises the question of whether technology is a facilitator or a hindrance to justice, underscoring the need for effective management in the legal system. The identification of potential rights violations in telematic hearings contributes to the ongoing discourse on how to strike a balance between safeguarding individual rights and ensuring judicial efficiency in the digital era. The constitutionally enshrined right to defense is a cornerstone of due process. The Ecuadorian Constitution guarantees free access to justice and adequate protection of rights and interests, thereby preventing defenselessness. Due process, the bedrock of the legal system, ensures a minimum procedure that upholds the existing legal framework. The right to appeal, a fundamental aspect of due process, enables the review of adverse rulings by higher courts, thereby ensuring the rectification of errors or injustices.